Mitochondrial Disorders Biochemical and Molecular Analysis - Wong, Ph.D., Lee-Jun C. (Methods in Molecular Biology, Methods and Protocols, 2012)
Due to the complexity of the mitochondrial system and the myriad genes involved in their function, the clinical manifestations of mitochondrial diseases are remarkably variable and heterogeneous. The laboratory and clinical methodologies used to evaluate dysfunction may vary widely, and thusly a systematic presentation of the numerous protocols that are applied to the assessment of these clinically and genetically heterogeneous disorders has proven to be essential.  Mitochondrial Disorders: Biochemical and Molecular Analysis strives to fill this need with a collection of key protocols provided by leading experts in the field.  Beginning with overviews of complexity of mitochondrial and nuclear genome disorders, the book continues with a section devoted to current biochemical protocols and a part focused on the DNA-based approaches used to identify molecular defects.  Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Detailed and authoritative, Mitochondrial Disorders: Biochemical and Molecular Analysis serves as a vital guide to researchers seeking to understand this incredibly complicated type of breakdown in cellular biology